Azerbaijan’s Aliyev Dynasty - Toghramadjian, Hagop (Colloquium: The Political Science Journal of Boston College, 2025)
Azerbaijan has been captured by the Aliyev family, which has turned the nation into its personal fiefdom since consolidating power in 1994. Current president Ilham Aliyev operates virtually unconstrained by any form of opposition: in addition to overseeing his father’s cult of personality, he has also pocketed hundreds of millions in state funds and changed the constitution to allow himself to stay on as president for life. How has Azerbaijan, a nation with a proud heritage as the first Muslim democracy, fallen into the grip of such a retrograde regime? This paper argues that the Aliyevs have successfully used a cocktail of oil wealth, nationalism and repression to keep themselves in power. But regime tactics are only part of the story: a key factor in Azerbaijan’s failure to democratize has been the astounding lack of external pressure and the international community’s problematic willingness to accept Aliyev regime narratives. Until this changes, the Azerbaijani people will likely continue to languish in the shadow of Heydar Aliyev and his enormously corrupt son.